Eco-Friendly Material Education with Tie Dye Technique For Ready-to-use Interior Products at Al-Mumtaza Orphanage - Isfiaty, Tiara; Aryani, Dewi Isma; Paqih, Rizqi Mohammad (Universitas Pendidikan Indonesia (UPI), 2025)
This study examines the applicability of strategies with educational methods through the use of eco-friendly materials in tie-dye training activities. The training activity served as a way to teach kids and young people from underrepresented groups at the Al-Mumtaza Orphanage in Bandung about the different kinds of eco-friendly materials and their applications. The activity was conducted to develop artistic creativity and knowledge of environmentally safe textile dyes used in ready-to-use interior products that are tie-dyed. With implications for curiosity and a desire to learn about environmental issues, both of which are critical to design, especially interior design, positive responses are expected. The methodology used combines content analysis with a descriptive qualitative approach. The content research approach (content analysis) is one of the ways used in dynamic processes to investigate and disclose the core based on educational strategy and methods. Qualitative research has two primary goals, which are to describe and explore, also to describe and explain. This is appropriate for describing the creation process and responses that take place throughout training sessions. The findings show that hands-on learning activities promote creativity, independence, and participants' motivation to improve. The findings also show that hands-on learning is at the heart of education's social purpose.